Gestational Exposure to Synthetic Steroid Hormones Impaired Sperm Quantity and Quality in Wistar Rats - Samy Ismail Ahmed; Aamir Magzoub; Mohammed Saeed Zayed Al-Ayed; Gamal Ali Attia; Basel A. Abdel-Wahab; Masood M. Khateeb; Asim M. Abdalla; Heitham M. Mohammed; Aymen N. Eldeen A. Elkareem; Ali Gadkarim A. Salih (International Journal of Endocrinology)
This study was designed to investigate the effect of prenatal exposure to synthetic sex steroid on sperm quantity and quality, relative testicular and epididymal weights, and reproductive hormones level in adult Wistar rats. Forty male Wistar rats were divided into two groups: a test group (n = 20) that included mature rats that were born to dams exposed to gestational treatment with hydroxyprogesterone and a control group (n = 20) that included mature rats born to untreated dams. Compared to the control group, the test group showed a significant reduction in the sperm count, viability and motility, relative testicular and epididymal weights together with increased abnormal spermatozoa (p<0.001). The reproductive hormonal assay revealed significantly lower serum testosterone and higher levels of FSH and LH among the test groups compared to the control (p<0.05 for all). Prenatal exposure to synthetic progesterone negatively affected sperm production and function, relative testicular and epididymal weights, and reproductive hormone levels.